A Study on the Development of Mathematical Literacy in the Topic of Systems of Linear Equations in Two Variables of Ninth Grade Students through Mathematical Modeling - Pavong, Sarunya; Tangkawsakul, Sakon; Somchaipeng, Tongta (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
Developing students’ mathematical literacy is a fundamental goal of 21st-century mathematics education. Organizing learning activities that enable students to engage in mathematical modeling from real-life situations presents significant challenges for mathematics teachers. This research aimed to examine the development of mathematical literacy among ninth-grade students through mathematical modeling activities on systems of linear equations with two variables. The participants were 35 ninth-grade students from an extended-opportunity school in Pathum Thani Province, Thailand, during the second semester of the 2024 academic year. The research instruments included eight lesson plans integrating mathematical modeling activities and four mathematical literacy assessment tests: one pre-test, two mid-tests, and one post-test. Data analysis employed descriptive statistics and content analysis. The research findings revealed that: 1. Students demonstrated continuous improvement in mathematical literacy, with post-test mean scores ( = 57.4) relatively higher than pre-test scores ( = 30.11), showing consistent developmental progress throughout the learning period. 2. Students exhibited clear development in formulating, successfully analyzing relevant information, model with equations aligned with problem situations, and solving problems more accurately and comprehensively. The research shows that the use of real-world problem situations with over-determined information related to students’ everyday experiences effectively promotes the development of sub-abilities within mathematical literacy. These findings suggest that integrating mathematical modeling activities can enhance students’ mathematical literacy and provide valuable insights for improving mathematics instruction in secondary education.